Bouncing Back from Setbacks: On the Mediating Role of Team Resilience in the Relationship Between Transformational Leadership and Team Effectiveness. Issue 6 (18th August 2018) - Dimas, Isabel Dórdio; Rebelo, Teresa; Lourenço, Paulo Renato; Pessoa, Carina Isabel Pereira
ABSTRACT: The purpose of this study was to clarify the role of team resilience on different facets of effectiveness (team viability and quality of the group experience). Moreover, given the importance of team resilience for the organizational context, it was also our aim to contribute to the study of the conditions that promote team resilience, analyzing the role of transformational leadership. Finally, we examined whether the relationship between transformational leadership and team resilience stimulates positive team outcomes. Ninety teams (445 employees from 40 companies) were surveyed and path analysis was used in the test of the hypotheses. The results showed a positive direct effect of team resilience on both team viability and the quality of the group experience. Moreover, a positive relationship was also identified between transformational leadership and team resilience. Finally, support was found for the mediated effect of team resilience on the relationship between transformational leadership and the dimensions of team effectiveness considered. The findings of this study highlight the role of team resilience as an intervening process between transformational leadership and team effectiveness. Supervisors should promote team resilience, adopting transformational leadership behaviors, in order to contribute to increase team viability and the quality of the group experience.